Early Life Professional and Layperson Support Reduce Poor Oral Hygiene Habits in Toddlers-A Prospective Birth Cohort Study - Diep Hong Ha; Loc Giang Do (MDPI AG, 2018)
Oral health behaviours of children are formulated from a very young age. Formation of those behaviours among very young children is dependent on their mothers/caregivers who may themselves require support from the health profession or laypersons. The study aimed to investigate if early life visits for check-up and dental advice and perceived support improved oral health behaviours as practiced by mothers of toddlers aged 24–30 months old. Data from a population-base birth cohort study in South Australia was used. The study recruited and followed mothers of newborn children from birth to age 24–30 months. Parental questionnaires collected information about socioeconomic factors, dental visiting patterns, and oral health behaviours as practiced by the mothers for their child. Self-reported putting a child to bed with a bottle and brushing a child’s teeth were the outcome variables. The two main exposures of this study were (1) early visiting for a dental advice, and (2) layperson support that a mother received in the first two years of having the child. Data were analysed progressively from bivariate to multivariable regression models. A total of 1183 mother/child dyads had complete data. The retained sample was representative of the population. Approximately 36% of mothers put their child to bed with a bottle and 26% of mothers did not brush their child’s teeth the night before. Around 29% of children had a visit for dental check-up and 80% of mothers reported having lay support. There were gradients in the outcome variables by socioeconomic factors and the main exposures. Multivariable regression models reported that having no dental visit for advice and having no lay support were associated with 1.30 and 1.21 imes higher rates of putting a child to bed with a bottle, respectively. Having no dental visit for advice was associated with a 1.37-times higher rate of not brushing a child’s teeth, controlling for other factors. This population-based birth cohort study confirmed importance of early life dental visit for check-up and support for mothers of young children in establishing oral health behaviours of young children.